Peptide Antibodies Methods and Protocols - Houen, Gunnar; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This extensive volume covers basic and advanced aspects of peptide antibody production, characterization, and uses. Although peptide antibodies have been available for many years, they continue to be a field of active research and method development. For example, peptide antibodies which are dependent on specific posttranslational modifications are of great interest, such as phosphorylation, citrullination, and others, while different forms of recombinant peptide antibodies are gaining interest, notably nanobodies, single chain antibodies, TCR-like antibodies, among others. Within this volume, those areas are covered, as well as several technical and scientific advances: solid phase peptide synthesis, peptide carrier conjugation and immunization, genomics, transcriptomics, proteomics and elucidation of the molecular basis of antigen presentation and recognition by dendritic cells, macrophages, B cells and T cells. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and authoritative, Peptide Antibodies: Methods and Protocols serves as an ideal reference for researchers exploring this vital and expansive area of study.
Peptide Antibodies: Past, Present, and Future -- The Structure of Natural and Recombinant Antibodies -- Prediction of Antigenic B and T Cell Epitopes Via Energy Decomposition Analysis: Description of the Web-Based Prediction Tool BEPPE -- Prediction of Antibody Epitopes -- Fmoc Solid-Phase Peptide Synthesis -- Peptide-Carrier Conjugation -- Solid Phase Peptide-Carrier Conjugation -- Analysis of Peptides and Conjugates by Amino Acid Analysis -- Characterization of Synthetic Peptides by Mass Spectrometry -- Interpretation of Tandem Mass Spectrometry (MSMS) Spectra for Peptide Analysis -- Polyclonal Peptide Antisera -- Production and Screening of Monoclonal Peptide Antibodies -- Production of Epitope-Specific Antibodies by Immunization with Synthetic Epitope Peptide Formulated with CpG-DNA-Liposome Complex Without Carriers -- Thioredoxin-Displayed Multipeptide Immunogens -- The Purification of Natural and Recombinant Peptide Antibodies by Affinity Chromatographic Strategies -- Isolation of Camelid Single-Domain Antibodies Against Native Proteins Using Recombinant Multivalent Peptide Ligands -- Generation of TCR-Like Antibodies Using Phage Display -- Structural Characterization of Peptide Antibodies -- Automated High Throughput Mapping of Linear B Cell Epitopes Using a Statistical Analysis of High Density Peptide Microarray Data -- Characterization of Peptide Antibodies by Epitope Mapping Using Resin-Bound and Soluble Peptides -- Screening and Characterization of Linear B-Cell Epitopes by Biotinylated Peptide Libraries -- Bead-Based Peptide Arrays for Profiling the Specificity of Modification State-Specific Antibodies -- Surface Plasmon Resonance Method to Evaluate Anti-Citrullinated Protein/Peptide Antibody Affinity to Citrullinated Peptides -- Specificity Analysis of Histone Modification Specific Antibodies or Reading Domains on Histone Peptide Arrays -- Prion-Specific Antibodies Produced in Wild-Type Mice -- Immunoblotting with Peptide Antibodies: Differential Immunoreactivities Caused by Certain Amino Acid Substitutions in a Short Peptide, and Possible Effects of Differential Refolding of the Peptide on a Nitrocellulose or PVDF Membrane -- Immunocytochemical and Immunohistochemical Staining with Peptide Antibodies -- Designing B-Cell Epitopes for Immunotherapy and Subunit Vaccines -- Enterovirus-Specific Anti-Peptide Antibodies -- Therapeutic HIV Peptide Vaccine.
Keywords: Immunology; Immunology